The complete works of Rtse-le Rgod-tshaṅ-pa Padma-legs-grub - Sna-tshogs-raṅ-grol, Rtse-le Rgod-tshaṅ-pa, b. 1608 (Mgon-po-tshe-brtan, 1979)
Writings of a Nyingmapa polymath of Koṅ-po in south-eastern Tibet.